THE USE OF POSTER MEDIA AS EARLY MARRIAGE EDUCATION - Siti Aminah; Sinta Rahmatil Fadhilah; Zakia Salma (El-Fatih: Jurnal Dakwah dan Penyuluhan Islam, 2025)
The high rate of early marriage is influenced by economic, social, cultural, and educational factors. The lack of awareness among adolescents about the consequences of early marriage increases the likelihood of young marriages, which negatively affect health and education. This study aims to evaluate the effectiveness of poster media in raising awareness among adolescents aged 15–19 about the risks of early marriage, psychological impacts, reproductive disorders, and the importance of continuing education. The research methodology uses a qualitative approach, involving group discussions, observation, interviews, documentation, and the use of educational posters to assess the knowledge and attitudes of adolescents. The findings indicate that the use of poster media in early marriage education significantly impacts the improvement of adolescents' awareness regarding the risks of marrying at a young age. The study, conducted with junior and senior high school students aged 15–19 in Sengeti Village, Muaro Jambi District, found that students perceived the poster messages as easily understandable and capable of raising awareness about the negative effects of early marriage, such as psychological barriers, reproductive health issues, and interrupted education. Education was delivered through material presentations, discussions, and the distribution of posters both in person and on social media, which motivated adolescents to continue their education, maintain appropriate social behaviors, and understand the risks of early marriage. This shows the effectiveness of socialization in shaping preventive thinking. In conclusion, education through posters and discussions effectively increases the awareness of adolescents aged 15-19 about the risks of early marriage, encourages prevention, promotes continuing education, and helps them understand its negative impacts.